Aesthetic replacement of malposed upper lateral incisor by implant supported ceramic crown - Saad Yasin Nori (University of Mosul, College of Dentistry, 2011)
Aims of the Study: To show the possibility of replacement of malposed upper lateral incisor by implant supported ceramic crown without raising a flap after extracting the tooth Materials and methods: An Implant of Xive type made by Dentsply - Friadent of diameter 3.4 and length 13 mm was implanted immediately after extraction of the malposed upper lateral incisor of a woman of 44 years old through the socket without raising a flap .A removable upper single tooth partial denture was inserted immediately after implant insertion. After 3 months period exposure of the implant was done and a gingival former was fixed for 2 weeks period after which an impression by elastic material was done after fixing transfer coping on the implant. A cast was made and a ceramic crown was made on the implant with proper shape and color and position which is fixed on the implant in the patient mouth. Results:The ceramic crown which is supported by the implant gave a better aesthetic result than the malposed natural lateral incisor regarding shape and position in relation to the adjacent teeth. Conclusions: Malposed upper anterior tooth could be replaced by implant supported ceramic crown successfully with out raising a flap giving better aesthetic value than before.